The role of holistic nutritional properties of diets in the assessment of food system and dietary sustainability - Dave LA; Hodgkinson SM; Roy NC; Smith NW; McNabb WC (Taylor and Francis Group, 2023)
Advancing sustainable diets for nutrition security and sustainable development necessitates clear nutrition metrics for measuring nutritional quality of diets. Food composition, nutrient requirements, and dietary intake are among the most common nutrition metrics used in the current assessment of sustainable diets. Broadly, most studies in the area classify animal-source foods (ASF) as having a substantially higher environmental footprint in comparison to plant-source foods (PSF). As a result, much of the current dietary advice promulgates diets containing higher proportions of PSF. However, this generalization is misleading since most of these studies do not distinguish between the gross and bioavailable nutrient fractions in mixed human diets. The bioavailability of essential nutrients including β-carotene, vitamin B-12, iron, zinc, calcium, and indispensable amino acids varies greatly across different diets. The failure to consider bioavailability in sustainability measurements undermines the complementary role that ASF play in achieving nutrition security in vulnerable populations. This article critically reviews the scientific evidence on the holistic nutritional quality of diets and identifies methodological problems that exist in the way the nutritional quality of diets is measured. Finally, we discuss the importance of developing nutrient bioavailability as a requisite nutrition metric to contextualize the environmental impacts of different diets.
Keywords: Bioavailability; dietary guidelines; food biodiversity; healthy diets; nutrient quality; sustainable nutrition; Animals; Humans; Diet; Nutritional Status; Food; Nutritive Value; Zinc